Kinerja Pemasaran Berdasarkan Orientasi Pasar Melalui Inovasi Produk Pada UMKM Manufaktur di Kabupaten Bangkalan - Arief, Mohammad; Rosiawan, Rizki Wahyudha (Jurnal Ekonomi Modernisasi, 2018)
The relationship between market orientation and firm performance have been explored from a several researchers. Even so, there is a gap that can be developed from that relationship, especially if associated with the firm performance measured. This study aims to explore the relationship between market orientation and marketing performance with product innovation as a mediating variable. The data collected from 150 respondents with purposive sampling technique. The results showed that there is a positive relationship between market orientation and all of marketing performance measurement. Furthermore, the study also found that product innovation is mediating the relationship between market orientation and marketing performance. The implications of the research findings have been discussed and there are some recommendations for the future researchers.